Febuxostat Loaded Microballoons: A Novel Approach for Gastric Retention (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Febuxostat loaded microballoons (FEB-MBs) were formulated using a non-aqueous solvent evaporation method using Eudragit RS 100, HPMC K4 M as a polymer, and span 80 as a surfactant. The ratio of solvents like methanol and dichloromethane, liquid paraffin as a processing medium. The formulation was optimized by the Box-Behnken design. Optimized formulation was evaluated for particle size, entrapment efficiency, % buoyancy, Percentage yield, in-vitro release studies, and stability study. Mean particle size 80.11 ± 0.349, entrapment efficient 83.25 ± 0.526, and % buoyancy 92.41 ± 0.57 were found for optimized formulation. Scanning electron microscopy (SEM) image of formulation shows discrete particle size with smooth surface texture with a hollow space and spherical shape and particle size < 200 μm. The result of in-vitro study shows an improved rate of drug release for a longer period from FEB-MBs compared with pure drugs. This is due to increases in the surface area leads to increases in absorption. The stability study shows no significant change in microballoons of the optimized formulation after 30 days of storage as per ICH guidelines. This multi particulate system provides an excellent approach for sustained release of a medicament for longer, thereby reducing dose frequency.